Dążenie do świętości sługi Bożego Jerzego Ciesielskiego na podstawie listów do żony (Chartum 1969–1970) - Goździk, Paulina (Studia Pastoralne, 2020)
Jerzy Ciesielski (1929-1970) was the Venerable, a God’s servant. He was also a husband, father and an outstanding scientist, he contributed to the development of ferroconcrete constructions in Poland. For many years he served as a lecturer at the Cracow University of Technology. In 1969, he went to Chartum in Sudan, where he took the position of the so called „visiting professor”. In this article, several letters to his wife written from Chartum in the years 1969-1970 have been analysed according to three aspects: the Eucharist as the top and the source of a Christian’s spiritual life, the community, self-improvement rooted in prayers and in deep connection with God and finally professional work, which was treated by Jerzy Ciesielski as the natural law of the human nature giving us the possibility of sanctification and hope of unification with God.